Military Parents’ Efforts to Assist Children’s Online Learning During Covid-19 - Dita Ayu R Pratiwi; Ali Imran Sinaga; Salminawati Salminawati (Jurnal Basicedu, 2022)
Military parents with good discipline and firmness in educating their children, including parents who live in the Bukit Barisan Gaperta Military Command I complex in Medan, certainly have a good influence on the implementation of children's online learning. This study aims to describe the efforts of military parents in assisting children to learn online, as well as their roles as teachers, facilitators, motivators, and coaches. This study uses a type of field research with qualitative methods and a descriptive analysis approach. Data was collected using interview, observation, and documentation techniques as well as data analysis with data reduction techniques, presentation, and drawing conclusions. The results of this study indicate that the military's efforts towards online learning are: 1) as teachers, parents act as educators, mentors, and companions in learning; 2) as facilitators, parents play a role in providing online learning facilities, channeling information between teachers and students, and providing other supporting educational facilities; 3) as a motivator, parents act as a support system, provide rewards, and motivators to encourage good faith, character, and worship; 4) as coaches, parents act as supervisors in learning, provide punishment that educates, applies discipline, and is firm in making decisions.